Contrasting biogeographic and diversification patterns in two Mediterranean-type ecosystems. - Sven Buerki; Sarah Jose; Shrirang R Yadav; Peter Goldblatt; John C Manning; Félix Forest (PLoS ONE, 2012)
The five Mediterranean regions of the world comprise almost 50,000 plant species (ca 20% of the known vascular plants) despite accounting for less than 5% of the world's land surface. The ecology and evolutionary history of two of these regions, the Cape Floristic Region and the Mediterranean Basin, have been extensively investigated, but there have been few studies aimed at understanding the historical relationships between them. Here, we examine the biogeographic and diversification processes that shaped the evolution of plant diversity in the Cape and the Mediterranean Basin using a large plastid data set for the geophyte family Hyacinthaceae (comprising ca. 25% of the total diversity of the group), a group found mainly throughout Africa and Eurasia. Hyacinthaceae is a predominant group in the Cape and the Mediterranean Basin both in terms of number of species and their morphological and ecological variability. Using state-of-the-art methods in biogeography and diversification, we found that the Old World members of the family originated in sub-Saharan Africa at the Paleocene-Eocene boundary and that the two Mediterranean regions both have high diversification rates, but contrasting biogeographic histories. While the Cape diversity has been greatly influenced by its relationship with sub-Saharan Africa throughout the history of the family, the Mediterranean Basin had no connection with the latter after the onset of the Mediterranean climate in the region and the aridification of the Sahara. The Mediterranean Basin subsequently contributed significantly to the diversity of neighbouring areas, especially Northern Europe and the Middle East, whereas the Cape can be seen as a biogeographical cul-de-sac, with only a few dispersals toward sub-Saharan Africa. The understanding of the evolutionary history of these two important repositories of biodiversity would benefit from the application of the framework developed here to other groups of plants present in the two regions.